The emerging high entropy materials for energy storage and conversion: Recent advances and future perspectives - Fangfei Lin; Runzhe Yao; Liyi Liu; Mengli Zhao; Junheng Wang; Fei Kang; De Li; Daming Chen; Panpan Zhang; Xing Lu; Yong Chen; Yaqing Wei (Chemical Engineering Journal, 2026)

Temperature and osmotic pressure dual-stimuli-responsive ophthalmic gels embedded with HPCD-modified nanoparticles for prolonged-release delivery of natamycin - Bixia Lin; Fangfei Fan; Hui Xu; Xin Li; Yufei Li; Chunya Qin; Xiaoyun Zhang; Shiqiang Zhang; Yang Gao; Lirong Niu (Drug Delivery and Translational Research, 2026)

A superhydrophobic-superhydrophilic sponge evaporator based on dragonfly biomimetic structure for efficient seawater desalination - Liwei Lin; Changqing Wu; Minghao Pan; Peijin Wu; Jiayi Deng; Zhaozu Liu; Fangfei Liu; Man Zhou; Song Xu; Yuzhe Zhang (Process Safety and Environmental Protection, 2026)

Rational design of high entropy metal phosphide anode for highly reversible lithium storage - Liyi Liu; Xuhao Liu; Jianqiu Zhu; Zhihui Huo; Bin Chen; Wei Liang; Mingeng Li; Fangfei Lin; Mengli Zhao; De Li; Daming Chen; Zhen Wang; et al. (Chemical Engineering Journal, 2026)

Charge-engineered 2D layered magnetic Cl-CaFe2O4/g-C3N4 catalyst for catalytic ozonation of norfloxacin: performance, mechanism and ecotoxicological assessment - Lanhe Zhang; Bing Shi; Hui Liu; Xu Lin; Fangfei Shi (Chemical Engineering Journal, 2025)

The environmental and economic effects of differentiated carbon tax across industries under the constraint of the “dual carbon” goal: A study based on a dynamic CGE model - Xiaobo Shen; Fangfei Zhang; Boqiang Lin (Journal of Environmental Management, 2025)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Identification of water pollution sources and analysis of pollution trigger conditions in Jiuqu River, Luxian County, China - Ying Liu; Fangfei Liu; Zhengjiang Lin; Nairui Zheng; Yu Chen (Environmental Science and Pollution Research, 2024)

High-breathable, antimicrobial and water-repellent face mask for breath monitoring - Fangfei Zhang; Junzhu Lin; Mingwan Yang; Yun Wang; Zhicheng Ye; Jiajun He; Jie Shen; Xuechang Zhou; Zhiguang Guo; Yabin Zhang; Ben Wang (Chemical Engineering Journal, 2023)

Cortical 3-hinges could serve as hubs in cortico-cortical connective network - Tuo Zhang; Xiao Li; Xi Jiang; Fangfei Ge; Shu Zhang; Lin Zhao; Huan Liu; Ying Huang; Xianqiao Wang; Jian Yang; Lei Guo; Xiaoping Hu; et al. (Brain Imaging and Behavior, 2020)
Mapping the relation between cortical convolution and structural/functional brain architectures could provide deep insights into the mechanisms of brain development, evolution and diseases. In our previous studies, we found a unique gyral folding pattern, termed a 3-hinge, which was defined as the conjunction of three gyral crests. The uniqueness of the 3-hinge was evidenced by its thicker cortex and stronger fiber connections than other gyral regions. However, the role that 3-hinges play in cortico-cortical connective architecture remains unclear. To this end, we conducted MRI studies by constructing structural cortico-cortical connective networks based on a fine-granular cortical parcellation, the parcels of which were automatically labeled as 3-hinge, 2-hinge (ordinary gyrus) or sulcus. On human brains, 3-hinges possess significantly higher degrees, strengths and betweennesses than 2-hinges, suggesting that 3-hinges could serve more like hubs in the cortico-cortical connective network. This hypothesis gains supports from human functional network analyses, in which 3-hinges are involved in more global functional networks than ordinary gyri. In addition, 3-hinges could serve as ‘connector’ hubs rather than ‘provincial’ hubs and they account for a dominant proportion of nodes in the high-level ‘backbone’ of the network. These structural results are reproduced on chimpanzee and macaque brains, while the roles of 3-hinges as hubs become more pronounced in higher order primates. Our new findings could provide a new window to the relation between cortical convolution, anatomical connection and brain function.

Correction to: CircUBAP2 promotes SEMA6D expression to enhance the cisplatin resistance in osteosarcoma through sponging miR-506-3p by activating Wnt/β-catenin signaling pathway - Xuelian Gong; Wei Li; Lin Dong; Fangfei Qu (Journal of Molecular Histology, 2020)
The authors of the article want to add Xuelian Gong and Wei Li as the first author and co-first author as they have greatly contributed to the revision work. The correct author group is given in this Correction.

CircUBAP2 promotes SEMA6D expression to enhance the cisplatin resistance in osteosarcoma through sponging miR-506-3p by activating Wnt/β-catenin signaling pathway - Lin Dong; Fangfei Qu (Journal of Molecular Histology, 2020)
The occurrence of chemo-resistance is an essential reason for the high morbidity of osteosarcoma (OS) patients. Circular RNAs (circRNAs) have been involved in the regulation of chemo-resistance in cancers. Semaphorins 6D (SEMA6D) is abnormally expressed in many cancers. However, the roles of circUBAP2 and SEMA6D in the chemo-resistance of OS are still unclear. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the expression levels of circUBAP2, SEMA6D and microRNA-506-3p (miR-506-3p). The cisplatin resistance and proliferation of cells were evaluated by 3-(4, 5-dimethyl-2 thiazolyl)-2, 5-diphenyl-2- H -tetrazolium bromide assay. Western blot analysis was performed to measure the protein levels of Wnt/β-catenin signaling pathway biomarkers and SEMA6D. Also, the apoptosis, migration and invasion of cells were assessed by Flow cytometry and Transwell assays, respectively. Besides, Dual-luciferase reporter assay was used to verify the interaction between miR-506-3p and circUBAP2 or SEMA6D. We found that the expression levels of circUBAP2 and SEMA6D were increased in cisplatin-resistant OS tissues and cells. Knockdown of circUBAP2 inhibited the cisplatin resistance, silenced Wnt/β-catenin signaling pathway, hindered cell proliferation, migration and invasion, and promoted apoptosis in cisplatin-resistant OS cells, all of which could be reversed by overexpression of SEMA6D. MiR-506-3p could be sponged by circUBAP2 and could target SEMA6D. The suppression of miR-506-3p overexpression on the progression of OS cisplatin resistance could be reversed by SEMA6D overexpression, while miR-506-3p inhibitor also could invert the inhibitory effect of circUBAP2 silencing on the progression of OS cisplatin resistance. In conclusion, CircUBAP2 and SEMA6D played active roles in the progression of OS cisplatin resistance through miR-506-3p, which might provide some new ideas for studying the countermeasures of OS resistance.

Tunable and Nontoxic Fluorescent Probes Based on Carbon Dots for Imaging of Indole Propionic Acid Receptor in Plant Tissues in Situ - Bixia Lin; Ying Yu; Fangfei Liu; Yujuan Cao; Manli Guo (Journal of Fluorescence, 2017)

Effects of ginsenoside Re on rat jejunal contractility - Yongjian Xiong; Dapeng Chen; Bochao Lv; Fangfei Liu; Qiying Yao; Zeyao Tang; Yuan Lin (Journal of Natural Medicines, 2014)